Effect of Active Workstation Use on Workload, Task Performance, and Postural and Physiological Responses. Issue 1 (2nd January 2016) - Ghesmaty Sangachin, Mahboobeh; Gustafson, Woodrow W.; Cavuoto, Lora A.
Abstract : OCCUPATIONAL APPLICATION : We assessed workload and performance when using two active workstations. Our results, consistent with earlier evidence, indicates that active workstations do not increase physical activity at the expense of reduced performance and operator workload, if these workstations are used for simple tasks that do not require great attention or fine motor control. Active workstations also allowed for more variability in posture and reduced static posture. However, reinforcement of ergonomics recommendations in terms of reducing non-neutral postures may be necessary. TECHNICAL ABSTRACT Background : Over the past 30 years, work has become more sedentary due to increased computer desk work, which has led to the development of major health consequences such as obesity and diabetes. One promising intervention for decreasing sedentariness is the incorporation of active workstations. Objective : We investigated the impact of two active workstations (standing and walking) on workload, task performance, and postural and physiological responses during standard office work tasks. Methods : Using a counterbalanced, within-subjects design, 30 subjects (aged 23.2 [3.1] years) were tested in three workstations: sitting, standing, and walking. A battery of simulated office tasks, including mousing, keyboarding, and cognition tasks, were presented in a randomized order during each trial. Subjective workload was assessed using the NASA-Task Load Index. Performance outcomes included reaction time, number of errors, and total task time. Physiological responses included percent heart rate reserve and heart rate variability. Neck, trunk, and shoulder inclination angles were analyzed to identify differences between workstations with respect to working posture. Results : Compared to sitting, standing and walking both resulted in significantly higher objective measures of workload. While use of walking workstation led to significantly decreased performance on fine motor control tasks, standing did not reduce performance and resulted in improved mousing performance. Both standing and walking allowed for more variability in posture. There was also an indication of more deviation from idle sitting posture while standing and walking compared to sitting. Conclusions : This study contributes to the guidance needed for the use of active workstations, to take advantage of the potential health benefits without sacrificing performance or substantially increasing workload. A standing workstation, properly adjusted based on user anthropometry and ergonomics recommendations, decreased sedentary time, allowed for more postural variability, and enhanced performance on some mousing and cognition tasks, while perceived workload remained consistent with levels while seated.